2020
DOI: 10.1093/ofid/ofaa199
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction in Coronavirus Disease 2019 Patients: Observational Cohort Study and Systematic Review

Abstract: Background Olfactory dysfunction (OD) has been reported in coronavirus disease 2019 (COVID-19). However, there are knowledge gaps about the severity, prevalence, etiology, and duration of OD in COVID-19 patients. Methods Olfactory function was assessed in all participants using questionnaires and the butanol threshold test (BTT). Patients with COVID-19 and abnormal olfaction were further evaluated using the smell identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 41 publications
3
113
0
2
Order By: Relevance
“…However, we note that these symptoms of blocked nose and runny nose were only present in up to 30% of our patients with OTD, suggesting that whilst blocked nose can contribute to OTD, the majority of our patients’ OTD symptoms must be due to other non-obstructive causes. Chung et al’s [ 15 ] study demonstrated that half of their patients with OTD had patent olfactory clefts on imaging and this lends further support to non-obstructive causes of OTD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, we note that these symptoms of blocked nose and runny nose were only present in up to 30% of our patients with OTD, suggesting that whilst blocked nose can contribute to OTD, the majority of our patients’ OTD symptoms must be due to other non-obstructive causes. Chung et al’s [ 15 ] study demonstrated that half of their patients with OTD had patent olfactory clefts on imaging and this lends further support to non-obstructive causes of OTD.…”
Section: Discussionmentioning
confidence: 90%
“…In their study, they found that elevated levels of inflammatory cytokines were associated with reduced olfactory identification scores in patients with chronic rhinosinusitis. However, Chung et al [ 15 ] again found that only 17% of their patients with OTD had rhinorrhea or nasal congestion and minimal inflammatory infiltrates as seen in their nasal biopsy specimens. This would suggest that local inflammation is at best a contributing factor but not the sole factor.…”
Section: Discussionmentioning
confidence: 99%
“…For the systematic review, our group had recently conducted a review, [6] which searched PubMed articles published from 1st January 2020 to 22nd April 2020, using the keywords "SARS-CoV-2", "COVID-19", "2019-nCoV", "novel coronavirus" and "coronavirus disease". As an extension to this recent publication, another search will be performed for articles published on PubMed from 23rd April 2020 to 10th June 2020, which will include the same search terms.…”
Section: Search Strategymentioning
confidence: 99%
“…[3][4][5] In addition, COVID-19 was shown to be associated with olfactory disturbances, which has since been recognised as a common and important neurosensory impairment in COVID-19 infection. [6][7][8] Recent systematic reviews and meta-analyses regarding COVID-19-related olfactory dysfunction (OD) have found signi cant discordance between subjective reporting of smell changes and objective quantitation of olfaction, [9,10] suggesting that validated tools for the assessment of olfactory function, such as the butanol threshold test [11] and smell identi cation test [12], may be more sensitive in identifying smell disturbances in COVID-19 patients. Interestingly, one of the articles suggested that the prevalence of COVID-19-related OD is inversely related to the patients' age, implying that young patients are more prone to experience smell disturbances in SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In addition, COVID-19 was shown to be associated with olfactory dysfunction (OD), which has since been recognised as a common and important neurosensory impairment in COVID-19. [9][10][11] Recent systematic reviews and meta-analyses regarding COVID-19-related OD have found signi cant discordance between subjective reporting of smell changes and objective quantitation of olfaction, [12][13][14] suggesting that validated tools for the quantitative assessment of olfactory function, such as butanol threshold test (BTT) [15] and smell identi cation test (SIT), [16] may be more sensitive in identifying smell disturbances in COVID-19 patients. Interestingly, one article suggested that the prevalence of COVID-19related OD was inversely related to the patients' age, implying that young patients were more prone to experience smell disturbances in SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%